2019
DOI: 10.1523/eneuro.0094-19.2019
|View full text |Cite|
|
Sign up to set email alerts
|

New Concerns for Neurocognitive Function during Deep Space Exposures to Chronic, Low Dose-Rate, Neutron Radiation

Abstract: As NASA prepares for a mission to Mars, concerns regarding the health risks associated with deep space radiation exposure have emerged. Until now, the impacts of such exposures have only been studied in animals after acute exposures, using dose rates ∼1.5×10 5 higher than those actually encountered in space. Using a new, low dose-rate neutron irradiation facility, we have uncovered that realistic, low dose-rate exposures produce serious neurocognitive complications associated with impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 65 publications
(113 reference statements)
6
108
1
Order By: Relevance
“…Most preclinical data that led to the Probabilistic Risk Assessment of HZE particles being detrimental to cognition were from tests performed on young adult rodents (~2-3 months [mon] at exposure) 14 ; in many cases, age at testing was not reported 14 . To more accurately reflect the average age of astronauts, NASA now requires ground-based space studies to be performed in mature animals (~6-mon-old at irradiation) [14][15][16][17][18][19][20][21][22][23][24] . Indeed, some studies now directly compare the cognitive impact of HZE irradiation in early life vs. maturity [25][26][27][28] , although the results are mixed.…”
mentioning
confidence: 99%
“…Most preclinical data that led to the Probabilistic Risk Assessment of HZE particles being detrimental to cognition were from tests performed on young adult rodents (~2-3 months [mon] at exposure) 14 ; in many cases, age at testing was not reported 14 . To more accurately reflect the average age of astronauts, NASA now requires ground-based space studies to be performed in mature animals (~6-mon-old at irradiation) [14][15][16][17][18][19][20][21][22][23][24] . Indeed, some studies now directly compare the cognitive impact of HZE irradiation in early life vs. maturity [25][26][27][28] , although the results are mixed.…”
mentioning
confidence: 99%
“…The long-term effects of these doses of radiation on the CNS are largely unknown. Acharya et al exposed mice to chronic, low-dose-rate (1 mGy/day) radiation for 6 months to investigate how deep space travel could affect the CNS [152]. They found that the radiation exposure impaired cellular signaling in the hippocampus, a part tied to learning and memory, and the prefrontal cortex, which plays a role in higher cognitive functions, resulting in learning and memory impairments.…”
Section: Genome Instabilitymentioning
confidence: 99%
“…Statistical Analyses 26 Data are reported as mean ± s.e.m. Testing of data assumptions (for example, normal distribution, similar variation between control and experimental groups, etc.)…”
Section: Stereological Cell Quantificationmentioning
confidence: 99%
“…Most preclinical data that led to the Probabilistic Risk Assessment of HZE particles being detrimental to cognition and related behavior were from tests performed on young adult rodents (~2-3 months [mon] old at exposure) (23,25) ; in many cases, age of the animals tested was not even reported (23) . To more accurately reflect the average age of astronauts, NASA now requires ground-based space studies to be performed in mature animals (~6 mon old at start of irradiation) (23,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) . Second, type of behavioral test matters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation